Tenure, Experience, Human Capital, and Wages: A Tractable Equilibrium Search Model of Wage Dynamics - Bagger, Jesper; Fontaine, François; Postel-Vinay, Fabien; Robin, Jean-Marc (American Economic Review, 2014)
We develop and estimate an equilibrium job search model of worker careers, allowing for human capital accumulation, employer heterogeneity, and individual-level shocks. Wage growth is decomposed into contributions of human capital and job search, within and between jobs. Human capital accumulation is largest for highly educated workers. The contribution from job search to wage growth, both within and between jobs, declines over the first ten years of a career—the “job-shopping” phase of a working life—after which workers settle into high-quality jobs using outside offers to generate gradual wage increases, thus reaping the benefits from competition between employers. (JEL J24, J31, J63, J64)